Musical Performance Anxiety - Mlaj, Miša (Širjenje obzorij o poučevanju glasbe, 2025)
Musical performance anxiety (MPA) is a widespread yet under-researched issue that negatively impacts the confidence and performance quality of musicians across different ages and skill levels. This chapter examines the distinctions between tremors and anxiety, strategies for managing anxiety, and its connection to perfectionism. Perfectionism is particularly significant, as many musicians experience heightened anxiety due to high expectations. The chapter also explores the various symptoms of MPA, which manifest as physiological (e.g., increased heart rate, breathing difficulties, sweating), mental (e.g., fear, panic, stress), and behavioural (e.g., muscle rigidity, agitation) responses.